THE ROLE OF NOISE AS A HARMFUL FACTOR IN THE PRODUCTION OF SOLID DOSAGE FORMS - Iskandarov A. B.; G‘obborova Sh. I. (Web of Journals Publishing, 2025)
This article examines the noise levels present in the production environment at key workplaces during the manufacturing of solid dosage forms and evaluates noise as a harmful occupational factor. The research findings demonstrate the detrimental effects of noise on workers’ health and emphasize the need to develop scientifically grounded and effective preventive measures to mitigate these impacts. The article also proposes innovative approaches aimed at reducing noise levels in accordance with occupational safety and sanitary-hygienic requirements. This analysis is of significant importance for improving working conditions and preventing occupational diseases in pharmaceutical manufacturing enterprises.
Keywords: Pharmaceutical enterprise, solid dosage forms, technological process, harmful factors, industrial noise, preventive measures.